INFLUENCE OF TECHNOLOGICAL PARAMETERS ON LASER MARKING PROCESS OF COPPER SURFACES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Laser marking technology today is a key part of the production of many products and devices used in our daily lives. At the same time, for specific types of products, the process must be optimized depending on the material used, laser system and marking method. Copper is such a metal that has a number of applications in the military industry, electrical engineering, electronics, household, etc. The scientific report investigates the influence of the technological parameters speed, raster step and number of repetitions on the contrast and roughness of marking for copper samples. A fiber laser technology system was used to perform the experiments, and the roughness measurements were performed with an OLS 5000 laser microscope. A wide range of marking speeds from 10 mm/s to 1500 mm/s was selected, where the contrast and roughness behavior of the marking is tracked for different raster steps in both single marking and double marking. It was found that as the speed increased, the contrast and roughness decreased. Also, with double marking, the contrast and roughness values are higher than with single marking. The velocity intervals in which the contrast has positive values and those in which it has negative values are established. The regularity was obtained that increasing the step of the raster leads to a decrease in contrast and an increase in roughness.